Discovery of 1′-(1-phenylcyclopropane-carbonyl)-3H-spiro[isobenzofuran-1, 3′-pyrrolidin]-3-one as a novel steroid mimetic scaffold for the potent and tissue-specific inhibition of 11β-HSD1 using a scaffold-hopping approach. (1st August 2022) - Zhang, Colin; Xu, Meizhong; He, Chunhong; Zhuo, Jincong; Burns, David M.; Qian, Ding-Quan; Lin, Qiyan; Li, Yun-Long; Chen, Lihua; Shi, Eric; Agrios, Costas; Weng, Linkai; et al.
Graphical abstract: Abstract: 11β-hydroxysteroid dehydrogenase 1 (11β-HSD1) has been identified as the primary enzyme responsible for the activation of hepatic cortisone to cortisol in specific peripheral tissues resulting in the concomitant antagonism of insulin action within these tissues. Dysregulation of 11β-HSD1, particularly in adipose tissues, has been associated with metabolic syndrome and type 2 diabetes mellitus. Therefore, inhibition of 11β-HSD1 with a small nonsteroidal molecule is therapeutically desirable. Implementation of a scaffold-hopping approach revealed a three-point pharmacophore for 11β-HSD1 that was utilized to design a steroid mimetic scaffold. Reiterative optimization provided valuable insight into the bioactive conformation of our novel scaffold and led to the discovery of INCB13739. Clinical evaluation of INCB13739 confirmed for the first time that tissue-specific inhibition of 11β-HSD1 in patients with type 2 diabetes mellitus was efficacious in controlling glucose levels and reducing cardiovascular risk factors.